GREEN BARRIERS IN INTERNATIONAL TRADE: A POLICY ANALYSIS OF THE EUROPEAN UNION DEFORESTATION REGULATION IN REVIEW OF THE GATT TREATY - I Nyoman Giri Kusuma; I Gede Pasek Eka Wisanjaya (Transpublika Publisher, 2024)
The European Union Deforestation Regulation (EUDR) is a regulation introduced by the European Union that aims to address deforestation and forest degradation by preventing the entry of products that contribute to deforestation into the European market. The existence of strict requirements for commodities imported into the EU market has been considered to create green trade barriers that contradict the principle of free trade. This research aims to examine the EUDR policy in the review of the GATT 1994 agreement specifically to understand more deeply the position of green trade barriers and their relation to the EUDR policy. The research method used is normative legal research with a statutory approach (Statue Approach) and conceptual approach (Conceptual Approach). The results of this study state that the explanation of Article XX paragraphs (b) and (g) of the GATT Agreement can be used as a legal basis to justify the application of environmentally motivated barriers in international trade. In other words, environmentally friendly forms of trade barrier protection are legitimate under the GATT Agreement, even though such policies may deviate from the principles of free trade, provided that such policies are not used as a means for unfair discrimination or restriction of trade.